Animation of BPMN business processes models - Roque, Marco André Marques (2014)
BPM in the business world is currently supported by tools that facilitate the design, implementation, execution, monitoring and optimization of business processes. These so called Business Process Management Suites usually have animation capabilities associated to process simulation. However, animation capabilities vary depending on the tool and the better these are, the higher is the animation preparation effort. This problem is more evident when generic simulation tools are compared with BPM specific ones, which use BPMN (Business Process Modeling Notation) as the modeling notation and have more limited animation capabilities. This dissertation presents a proposal to endow the BPMN with animation capabilities which respects all the elements presentation rules established in the notation specification. This proposal was designed based upon the data collected through the application of the animation capabilities evaluation taxonomy also proposed here in this dissertation. A prototype was built on top of an open-source tool in order to implement our animation proposal and was used to animate the service request process model using real execution data from an IT Service management tool used at ISCTE-IUL.